1989
DOI: 10.1007/bf01908205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between isomyosin pattern and contractility of right ventricular myocytes isolated from rats with right cardiac hypertrophy

Abstract: The contractile properties of single rat cardiac cells isolated from normal and hypertrophied right ventricles have been investigated. These have been correlated with the isoenzyme composition of the whole ventricle. Right cardiac hypertrophy was induced by injecting rats with monocrotaline, an alkaloid which induces severe pulmonary hypertension. Ca2+ ATPase activity and myosin alpha-chain percentage were decreased in the hypertrophied right ventricle as compared with that of control rats. The contraction amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…MCT-treated rats presented myosin heavy-chain isoform switch in the LV myocardium. The slower b-isoform was increased in the LV of both MCT-4 and MCT-6, as previously reported in different models of RV hypertrophy [17,43,46,47]. Changes in the expression of enzymes involved in bioenergetics and cell metabolism such as pyruvate dehydrogenase kinase-4, acetyl-CoA dehydrogenase and mitochondrial ATP synthase [42,43] as well as a reduced capillary proliferation [21] have also been described in the LV of PH rats.…”
Section: Edlvp) B End Diastolic LV Dimensions (Edlvd)supporting
confidence: 72%
“…MCT-treated rats presented myosin heavy-chain isoform switch in the LV myocardium. The slower b-isoform was increased in the LV of both MCT-4 and MCT-6, as previously reported in different models of RV hypertrophy [17,43,46,47]. Changes in the expression of enzymes involved in bioenergetics and cell metabolism such as pyruvate dehydrogenase kinase-4, acetyl-CoA dehydrogenase and mitochondrial ATP synthase [42,43] as well as a reduced capillary proliferation [21] have also been described in the LV of PH rats.…”
Section: Edlvp) B End Diastolic LV Dimensions (Edlvd)supporting
confidence: 72%
“…In * * o a both animal and human studies on P-adrenoceptor desen-/ * Z sitization we have shown by ANOVA that the within-subject T/ variability for isolated cells is much less than the between-0 /ozl subject (Jones et al, 1990a,b;Harding et al, 1990a). In two T/ //1 animal models of heart failure we have observed changes in t~* //either biochemical parameters or receptor response which /1 // closely parallel those seen in the whole ventricle (Vescovo et al, 1989a;Jones et al, 1990b).…”
Section: Discussionmentioning
confidence: 61%
“…Adult male Sprague-Dawley rats (250–300 g) cardiomyocytes were isolated by the Langendorff perfusion method, as previously described ( 26 ). After isolation, cardiomyocytes from the left ventricle were plated on laminin-coated coverslips and left to adhere for at least 45 min before the start of experiments.…”
Section: Methodsmentioning
confidence: 99%